2019
DOI: 10.21660/2019.63.48290
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Erosion Using Hydroseeding on Post Coal Mining in Melak Site

Abstract: After the mining process, Melak coal mining conducts reclamation. One of the problems is the steep slope caused by the coal exploitation process. The slope is difficult to be replanted and the soil is easily eroded by rainwater. The hydroseeding combined with jute net method has been applied in this area, but the effectiveness and success of using that method have not been measured accurately. Therefore, this study aims to examine e x p li c it l y the effectiveness of hydroseeding combined with jute net metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Together with Centrosema pubescens, Pueraria javanica, and Calopogonium mucunoides, P. javanica was able to reduce cumulative sediment by 89.57% at the disposal site and 96.62% at a low wall in a pit when the jute net method was used. This means that this method has proven effective in reducing erosion for post-mining areas (Bargawa et al 2019). Other studies have shown that P. javanica is a type of vegetation that has better growth.…”
Section: Discussionmentioning
confidence: 94%
“…Together with Centrosema pubescens, Pueraria javanica, and Calopogonium mucunoides, P. javanica was able to reduce cumulative sediment by 89.57% at the disposal site and 96.62% at a low wall in a pit when the jute net method was used. This means that this method has proven effective in reducing erosion for post-mining areas (Bargawa et al 2019). Other studies have shown that P. javanica is a type of vegetation that has better growth.…”
Section: Discussionmentioning
confidence: 94%
“…The hydroseeding technique could be used for planting species of Leguminosae (Cajanus cajan, Crotalaria pallida, D. triflorum, Indigofera spicata, Sesbania grandiflora), Poaceae (Eleusine indica, Sporobolus indicus, P. conjugatum), and Cyperaceae (Cyperus brevifolius, C. odoratus, Kyllingia monocephala) in Tanah Laut, South Kalimantan, Indonesia [106]. This technique was applied and combined with a jute net for planting C. mucunoides, C. pubescens, and P. javanica, on the steep slope, where it was difficult to replant it, where the soil was easily eroded by rainwater due to the coal exploitation process [107]. The hydroseeding application on post-coal-mining landscapes is presented in Figures 6 and 7.…”
Section: Species Selectionmentioning
confidence: 99%
“…Studies [5][6][7] address the issue of realization of precision seeding and improvement of the process of seeding germinated seeds of agricultural crops.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%